The mechanism of oxytocin and its receptors in regulating cells in bone metabolism - Feixiang, Liu; Yanchen, Feng; Xiang, Li; Yunke, Zhang; Jinxin, Miao; Jianru, Wang; Zixuan, Lin (Frontiers in Pharmacology, 2023)
Oxytocin (OT) is a neuropeptide known to affect social behavior and cognition. The epigenetic modification of the oxytocin receptor (OTR) via DNA methylation stimulates parturition and breast milk secretion and inhibits craniopharyngioma, breast cancer, and ovarian cancer growth significantly as well as directly regulates bone metabolism in their peripheral form rather than the central form. OT and OTR can be expressed on bone marrow mesenchymal stem cells (BMSCs), osteoblasts (OB), osteoclasts (OC), osteocytes, chondrocytes, and adipocytes. OB can synthesize OT under the stimulation of estrogen as a paracrine–autocrine regulator for bone formation. OT/OTR, estrogen, and OB form a feed-forward loop through estrogen mediation. The osteoclastogenesis inhibitory factor (OPG)/receptor activator of the nuclear factor kappa-B ligand (RANKL) signaling pathway is crucially required for OT and OTR to exert anti-osteoporosis effect. Downregulating the expression of bone resorption markers and upregulating the expression of the bone morphogenetic protein, OT could increase BMSC activity and promote OB differentiation instead of adipocytes. It could also stimulate the mineralization of OB by motivating OTR translocation into the OB nucleus. Moreover, by inducing intracytoplasmic Ca2+ release and nitric oxide synthesis, OT could regulate the OPG/RANKL ratio in OB and exert a bidirectional regulatory effect on OC. Furthermore, OT could increase the activity of osteocytes and chondrocytes, which helps increase bone mass and improve bone microstructure. This paper reviews recent studies on the role of OT and OTR in regulating cells in bone metabolism as a reference for their clinical use and research based on their reliable anti-osteoporosis effects.